Pendampingan Pembuatan Konten Multimedia untuk Pelaku UMKM di Kecamatan Ilir Barat II, Kota Palembang - Nyimas Dewi Murnila Saputri; Agung Putra Raneo; Muhammad Ichsan Hadjri (Sriwijaya Accounting Community Services, 2023)
The aim of this service activity is to provide counseling and assistance regarding the creation of multimedia content to MSMEs in Ilir Barat II District, Palembang City. The implementation of this Community Service activity is carried out using the method of distributing materials, lectures, and discussions/questions and answers. The results of this activity show that participants are increasingly educated and skilled in applying multimedia concepts in developing their businesses.